Intertextual References and the Literary Canon in Children’s Literature - Haramija, Dragica (Slavia Centralis, 2023)
The article focuses on different forms of intertextuality in children’s literature. To link the intellectual elements, one needs to possess the knowledge of canonical texts. Without this, contemporary literary texts that contain such elements might not function well. Also, lack of knowledge of the source text can result in part of the story being lost. The present article demonstrates different intertextual connections on the example of selected stories involving the metamorphosis of a frog as the main literary and (apart from Lila Prap) also the title character. The source text is The Frog Prince or Iron Henry by Brothers Grimm, while the works studied are Saša Vegri’s Jure kvak kvak (George Croak, Croak), Lila Prap’s 1001 pravljica (1001 Stories), Bina Štampe Žmavc’s O žabi in princu (About a Frog and a Prince) and Andrej Rozman Roza’s O začaranem žabcu (About the Enchanted Frog).
Keywords: literary canon, intertextuality, meme, metamorphosis, fairy tale, frog